Pengenaan Sanksi Pidana Denda Bagi Orang Yang Menolak Untuk Divaksin - Rivaldo Laimeheriwa; Deassy Jacomina Anthoneta Hehanussa; Jacob Hattu (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: People still feel unsafe and refuse vaccines to prevent Covid-19.Purposes of the Research: This review aims to discuss and analyze the imposition of criminal sanctions, fines and refusal of vaccines as being categorized as criminal acts.Methods of the Research: This writing is yuridis normatif.ast the Statute Approach, Conceptual Approach,and Case Approach sources of legal materials use in research on legal materials primer,legal materials sekunder.supporting data and information are identified and the systematicallyanalyzed for interpretation abd argumentation to gt conclusion about the problemResults of the Research: Thet imposition of fine for vaccine refusal is a criminal sanction that basically guarantees the rehabilitation of prepetratros, but fine are often imposed as a threat to human freedom